Determinants of Consumer’s Willingness to Purchase Gray-Market Smartphones - Liao, Chun-Hsiung; Hsieh, I. -Yu (2013)
The study analyzes the influential factors of consumers’ willingness to purchase gray-market smartphones by considering the model of novelty seeking, status consumption, integrity, and perceived risk. Attitude toward counterfeit is used as mediation in the model. The causalities in the model of problematic willingness of consumer to purchase gray-market smartphones are hypothesized. A total sample of 350 respondents with 238 effective samples is collected by interviewing with questionnaires at the service counters of telecommunications operators. Structure equation modeling (SEM) is adopted in the analysis. Consumers’ attitude toward counterfeit goods is found to be positively related to the willingness of consumers to purchase gray-market smartphones, but perceived risk is negatively related to consumers’ willingness to purchase. As for personality constructs, integrity and status consumption are found to be negatively related to consumers’ attitude toward counterfeit goods, but novelty seeking is positively related to the attitude. Further, managerial implications for branded smartphone manufacturers and telecommunications regulators are provided by the research.
Keywords: perceived risk; Novelty seeking; Attitude toward counterfeit goods; Willingness to purchase; Gray-market smartphone